Is the Atlantic a Source for Decadal Predictability of Sea-Level Rise in Venice? - Zanchettin D.; Rubinetti S.; Rubino A. (Earth and Space Science, 2022)
Sea-level rise is one of the most critical consequences of global warming, with potentially vast impacts on coastal environments and societies. Sea-level changes are spatially and temporally heterogeneous on multiannual-to-multidecadal timescales. Here, we demonstrate that the observed rate of winter sea-level rise in the Italian city of Venice contains significant multidecadal fluctuations, including interdecadal periods of near-zero trend. Previous literature established a connection between the local sea-level trend in Venice and over the broad subpolar and eastern North Atlantic. We demonstrate that for multidecadal variations in sea-level trend such connection holds only since the mid-20th Century. Such multidecadal sea-level fluctuations relate to North Atlantic sea-surface temperature changes described by the Atlantic multidecadal variability, or AMV. The link is explained by combined effect of AMV-linked steric variations in the North Atlantic propagating in the Mediterranean Sea, and large-scale atmospheric circulation anomalies over the North Atlantic with a local effect on sea level in Venice. We discuss the implications of such variability for near-term predictability of winter sea-level changes in Venice. Combining available sea-level projections for Venice with a scenario of imminent AMV cooling yields a slowdown in the rate of sea-level rise in Venice, with the possibility of mean values remaining even roughly constant in the next two decades as AMV effects contrast the expected long-term sea-level rise. Acknowledging, understanding, and communicating this multidecadal variability in local sea-level rise is crucial for management and protection of this world-class historical site.Plain Language Summary Environmental and socioeconomic impacts of sea-level rise are one of the major concerns of global warming. Here, we consider the case of the Italian city of Venice, one of the iconic locations for the potentially dramatic effects of sea-level rise. We show that the sea-level evolution in Venice ...